The global youth anti-culture: realities, trends and implications for Malaysian youth research - Krauss, Steven Eric (Universiti Putra Malaysia Press, 2008)
This paper attempts to highlight some of the key issues pertaining to the advent of what is been coined “global culture,” and its impact on youth both in Malaysia and around the world. Global culture has become a reality in Malaysia due to the rapid globalization process that has burgeoned over the past two decades. This piece focuses particularly on the plight of young people within a dramatically changing world, with a particular emphasis on implications for youth research. Some of the topics covered include: the universal nature and rise of social ills among youth; the deteriorating state of the family in societies including Malaysia and its impact on youth; how youth are viewed and targeted by multinational corporate entities in an ever-increasing materialistic and consumerist world culture; the traditional status of youth in Western and Eastern societies and how that status is changing; and how today’s global culture impacts young peoples’ ability to carve out an identity for themselves. The paper concludes with general suggestions for the potential role of youth research as the primary mechanism for explaining the intricate issues facing young people as they attempt to grow and succeed in the modern world.